TINDAK PIDANA ILLEGAL LOGGING DAN UPAYA PENANGGULANGAN DITINJAU MENURUT PERPU NOMOR 1 TAHUN 2004 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG KEHUTANAN - ARMILA SELVIANI (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT That the modus operandi of theft above really makes it difficult for polhut officers to perform their duties, well, especially to face the risk of "life" that is likely to exist. So Modus Operandi of illegal logging in review by article 362 of the Criminal Code jo Inpres no. 4 Year 2005, has fulfilled the element of theft act and it must be done investigation or legal process and the act has also damaged the environment and will automatically bring the impact of the loss of the nation and the State. In this case through Presidential Instruction Number 4 Year 2005 on the criminal act of illegal logging, must be dealt with firmly do not recognize compromise and the action is a priority mandated through Inpres no. 4 Year 2005. In the framework of eradicating illegal logging in forest areas and its circulation throughout the territory of the Republic of Indonesia, it is instructed to all state apparatuses to take unequivocal action against illegal logging perpetrators. The legal process must be carried out consistently for the sake of law in this country. ( Law enforcement ) should be put forward.Factors causing criminal acts of illegal logging of timber products are: Economic population is relatively weak; Ironwood has high economic value; Ironwood theft is easy to do. The modus operandi of illegal timber theft in KPH East Kalimantan; Enter the forest area in the evening or evening; The perpetrators of timber theft are not just one night in the forest, but stay up for days; Conducted in groups. Efforts to control criminal acts of illegal logging. Prevention efforts in a preventive way. The counseling materials include: Environment, Transmigration, Job Skills, Legal Knowledge, Religious Lectures. Repetitive countermeasures In addition to prevention efforts above, the Perum Perhutani and the relevant agencies also perform repressive actions when the perpetrators of criminal acts of illegal logging are caught by investigating and investigating in the end Until sentenced from the district court.